2017
DOI: 10.3389/fpsyg.2017.01393
|View full text |Cite
|
Sign up to set email alerts
|

You Look Human, But Act Like a Machine: Agent Appearance and Behavior Modulate Different Aspects of Human–Robot Interaction

Abstract: Gaze following occurs automatically in social interactions, but the degree to which gaze is followed depends on whether an agent is perceived to have a mind, making its behavior socially more relevant for the interaction. Mind perception also modulates the attitudes we have toward others, and determines the degree of empathy, prosociality, and morality invested in social interactions. Seeing mind in others is not exclusive to human agents, but mind can also be ascribed to non-human agents like robots, as long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(76 citation statements)
references
References 94 publications
6
69
0
1
Order By: Relevance
“…For example, Wiese et al . demonstrated reduced gaze following when gaze cues were perceived as being delivered by a robot (e.g., a computer program performing predetermined behaviors) rather than a human agent . These effects are reflected in neural activity, with increased activation of the TPJ when gaze is perceived as human controlled, and reduced magnitudes of the event‐related P1 and N170 components when gaze is perceived as computer controlled.…”
Section: The Three Core Processesmentioning
confidence: 99%
“…For example, Wiese et al . demonstrated reduced gaze following when gaze cues were perceived as being delivered by a robot (e.g., a computer program performing predetermined behaviors) rather than a human agent . These effects are reflected in neural activity, with increased activation of the TPJ when gaze is perceived as human controlled, and reduced magnitudes of the event‐related P1 and N170 components when gaze is perceived as computer controlled.…”
Section: The Three Core Processesmentioning
confidence: 99%
“…In addition to the precise replication of human behavior, it seems to be important to consider the meaning of the behaviors of an agent from a metacommunication point of view. It is known that not only a human-like appearance but also natural behavior such as eye contact affects the perception of the agent by humans [39]. Changing the behavior of a robot (the ''embodied cues'') while interacting with a human affects the performance of the human [40].…”
Section: Towards a Human-like Conversational Agentmentioning
confidence: 99%
“…Several works [5] [6] have shown that learning a model for physical interactions can help robots learn faster in the real-world. Secondly, in social interactions, humans have little tolerance for random behaviors [7], and lose interest quickly if the model deviates too much from † Authors contributed equally. *This work is partly supported by the Swedish Research Council (grant n. 2015-04378) and partly by the COIN project (RIT15-0133) funded by the Swedish Foundation for Strategic Research.…”
Section: Introductionmentioning
confidence: 99%